Bionic coral reef and manufacturing method thereof

By using high-throughput bionic coral reefs made of materials such as blast furnace slag, the problem of existing bionic coral reefs being easily gnawed is solved, and efficient underwater microbial adhesion and long-term existence are achieved.

CN119841621AActive Publication Date: 2025-04-18KEDA INDUSTRIAL GROUP CO LTD

Patent Information

Application Number
CN202510337765.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-21
Publication Date
2025-04-18
Estimated Expiration
2045-03-21

AI Technical Summary

Technical Problem

Existing bionic coral reefs are easily gnawed by thorny starfish, resulting in failure and ineffective protection of the environment.

Method used

Materials such as blast furnace slag, feldspar, tailings, glass powder, clay and talc are used as raw materials, and silicon carbide is added as foaming agent. Through the firing process, bionic coral reefs with high throughput, small dry specific gravity and high water absorption are formed, and calcium carbonate is avoided.

Benefits of technology

The obtained bionic coral reef has high throughput, small dry specific gravity and high water absorption. It can quickly absorb water and sink into water, which is easy to install, and does not contain calcium carbonate and is not easily gnawed by long spiny starfish, effectively solving the problem of the existing bionic coral reefs being easily gnawed.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a bionic coral reef and a manufacturing method thereof, and belongs to the technical field of porous ceramics, raw materials for manufacturing the bionic coral reef comprise a first raw material and a second raw material, the first raw material comprises, by mass, 30-45% of blast furnace slag, 10-30% of feldspar, 15-30% of tailings, 5-10% of glass powder, 5-10% of clay and 5-10% of talcum powder; the second raw material comprises a foaming agent which accounts for 0.2-0.6% of the mass of the first raw material. The bionic coral reef has the advantages of being high in through hole rate, small in dry specific gravity and high in water absorption rate, does not contain calcium carbonate, and can effectively solve the problem that existing bionic coral is prone to being gnawed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of porous ceramics, and in particular relates to a bionic coral reef and a manufacturing method thereof. Background Art

[0002] Coral is the outer shell secreted by coral polyps, and its chemical composition is mainly calcium carbonate. Coral is composed of the calcareous skeletons of millions of coral polyps. It is mostly tree-like in shape with vertical stripes. Each single coral cross section has concentric and radial stripes. Coral reefs have a complex three-dimensional spatial structure, forming countless caves and gaps, providing many marine animals with places to lay eggs, reproduce and hide from enemies, which is conducive to improving the biodiversity of the ocean. In addition, coral reefs are natural coastal barriers that have the functions of dissipating wave energy, reducing coastal erosion, and protecting subtropical coastlines. Coral reefs are also a key link in material circulation and energy flow, which helps to improve the self-regulation ability of the marine environment.

[0003] Making bionic coral reefs to provide shelter for marine microorganisms is a common method. However, the current bionic coral reefs are still made of calcium carbonate as the main material. For example, the invention patent with publication number CN109169459A discloses an eco-friendly artificial mimic coral reef body that uses environmentally friendly unsaturated resin to make bionic coral reefs, and adds calcium carbonate powder. The invention patent with publication number CN114467806A discloses a cement coral sand mixed attachment base and its preparation and application method, collects coral sand and coral bones as pore-forming agents, and mixes silicate cement and coral sand / coral bones to make bionic coral reefs. Bionic coral reefs containing calcium carbonate will be eaten by long-spined sea stars. After a period of time, the bionic coral reefs will become ineffective and cannot effectively protect the environment. Summary of the invention

[0004] In order to solve the above technical problems, the purpose of the present invention is to provide a bionic coral reef and a method for making the same, which has the advantages of high through-porosity, small dry specific gravity and high water absorption rate, does not contain calcium carbonate, and can effectively solve the problem that the existing bionic corals are easily eaten.

[0005] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is as follows: In a first aspect of the present invention, the present invention provides a bionic coral reef, wherein the raw materials for making the bionic coral reef include a first raw material and a second raw material; In the first raw material, calculated by mass percentage, the first raw material includes 30-45% of blast furnace slag, 10-30% of feldspar, 15-30% of tailings, 5-10% of glass powder, 5-10% of clay and 5-10% of talc; The second raw material includes a foaming agent, and the foaming agent accounts for 0.2-0.6% of the mass of the first raw material.

[0006] Preferably, the components in the blast furnace slag are calculated by mass percentage, and the silicon dioxide content in the blast furnace slag is ≥30%, the aluminum oxide content is ≥10%, and the calcium oxide content is ≥30%.

[0007] Preferably, the components in the tailings are calculated by mass percentage, and the silicon dioxide content in the tailings is ≥60%, the aluminum oxide content is ≥10%, the potassium oxide content is ≥3%, and the sodium oxide content is ≥2%.

[0008] More preferably, the tailings comprise perlite tailings.

[0009] Preferably, the components in the clay are calculated by mass percentage, and the silicon dioxide content in the clay is ≥40%, the aluminum oxide content is ≥35%, the iron oxide content is ≥1%, and the titanium dioxide content is ≥0.5%.

[0010] More preferably, the clay comprises Kikuchi clay.

[0011] Preferably, the components in the feldspar are calculated by mass percentage, and the sum of potassium and sodium elements in the feldspar is ≥ 7% and the potassium content is ≥ 3%.

[0012] More preferably, the feldspar comprises potassium feldspar powder having a potassium content of ≥ 10%.

[0013] Preferably, the blowing agent comprises silicon carbide.

[0014] In a second aspect of the present invention, the present invention provides a method for making a bionic coral reef, as follows: The first raw material and the second raw material are mixed and ball-milled, and dried and powdered to obtain a raw material mixture, and then the raw material mixture is fired to obtain a bionic coral reef; The firing process is as follows: heating the raw material mixture to 600-650°C for 30-60 minutes; heating from 600-650°C to 890-910°C for 60-120 minutes; keeping warm at 890-910°C for 120-180 minutes; heating from 890-910°C to 1040-1060°C for 120-210 minutes; keeping warm at 1040-1060°C for 120-210 minutes; heating from 1040-1060°C to 1115-1135°C for 30-60 minutes; keeping warm at 1115-1135°C for 10-50 minutes.

[0015] Beneficial effects:

[0016] The bionic coral reef prepared by the present invention has the advantages of high through-porosity, small dry specific gravity and high water absorption rate. The small dry specific gravity is conducive to transportation, the high water absorption rate is conducive to the bionic coral reef quickly absorbing water and sinking into the water, and is easy to install. The high through-porosity is conducive to the attachment of underwater microorganisms to the holes. The product prepared based on the raw materials of the present invention does not contain calcium carbonate and is not food for long-spined sea stars. It can effectively solve the problem that the existing bionic corals are easily eaten, and is very suitable for use as bionic coral reefs. DETAILED DESCRIPTION

[0017] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the specific implementation methods of the present invention will be described below. Obviously, the following descriptions are only some embodiments of the present invention, and for those of ordinary skill in the art, other implementation methods can also be obtained based on these embodiments without creative work.

[0018] The present invention provides a bionic coral reef, wherein the raw materials for making the bionic coral reef include a first raw material and a second raw material; In the first raw material, calculated by mass percentage, the first raw material includes 30-45% blast furnace slag, 10-30% feldspar, 15-30% tailings, 5-10% glass powder, 5-10% clay and 5-10% talc; the second raw material includes a foaming agent, and the foaming agent accounts for 0.2-0.6% of the mass of the first raw material.

[0019] The bionic coral reef obtained by firing the raw materials of the present invention has the advantages of small dry specific gravity and high water absorption rate. The proportion of through-hole bubbles in the bionic coral reef of the present invention is not less than 50%. The small dry specific gravity of the bionic coral reef is conducive to transportation, and the high water absorption rate is conducive to the bionic coral reef to quickly absorb water and sink into the water (seabed), which is convenient for installation. The bionic coral reef prepared based on the raw materials of the present invention does not contain calcium carbonate and is not food for long-spined sea stars, which can effectively solve the problem that the existing bionic coral is easily eaten.

[0020] In the present invention, blast furnace slag can be solid waste formed by gangue in ore, ash in fuel and non-volatile components in solvent during blast furnace ironmaking. Preferably, the components in blast furnace slag are calculated by mass percentage, and the blast furnace slag selected by the present invention has a silicon dioxide content of ≥30%, an aluminum oxide content of ≥10%, and a calcium oxide content of ≥30%. Calcium oxide has the effect of reducing the firing temperature in the raw material formula, and a suitable amount of calcium oxide is conducive to forming a multi-through-hole structure.

[0021] In the present invention, the components in the tailings are calculated by mass percentage, and the tailings preferably have a silicon dioxide content ≥60%, an aluminum oxide content ≥10%, a potassium oxide content ≥3%, and a sodium oxide content ≥2%. More preferably, the tailings are perlite tailings, which can enhance the function of the product, making the product light and high-strength. In addition, the perlite tailings have a high silicon content, which can improve the green body structure and make the raw material formula more stable.

[0022] In the present invention, clay refers to fine-grained natural soil materials containing clay minerals. The components in the clay are calculated by mass percentage, and preferably the clay has a silicon dioxide content ≥40%, an aluminum oxide content ≥35%, a iron oxide content ≥1% and a titanium dioxide content ≥0.5%. For example, the clay is Mujie clay (clay rock mainly composed of kaolinite in standard coal-bearing strata, which is soft or semi-soft clay).

[0023] In the present invention, the components in the feldspar are calculated by mass percentage, and the feldspar is preferably a feldspar with a total potassium and sodium content of ≥7% and a potassium content of ≥3%, for example, commercially available potassium feldspar powder with a potassium content of ≥10% and a particle size of ≤0.074 mm.

[0024] In the present invention, the glass powder can be commercially available glass powder, and preferably glass powder with a particle size of ≤0.063 mm is used.

[0025] In the present invention, talc powder can be selected from commercial talc powder, for example, the components in the talc powder are calculated by mass percentage, and the talc powder has a silicon dioxide content of ≥30%, a magnesium oxide content of ≥35%, and a calcium oxide content of ≥1%. In the present invention, the talc powder is preferably raw talc powder.

[0026] In the present invention, the foaming agent includes silicon carbide powder, such as commercially available silicon carbide powder, with a particle size of ≤0.017 mm.

[0027] The present invention also proposes a method for making a bionic coral reef, as follows: The first raw material and the second raw material are mixed and ball-milled, and dried and powdered to obtain a raw material mixture, and then the raw material mixture is fired to obtain a bionic coral reef; The firing process is as follows: heating the raw material mixture to 600-650°C for 30-60 minutes; heating from 600-650°C to 890-910°C for 60-120 minutes; keeping warm at 890-910°C for 120-180 minutes; heating from 890-910°C to 1040-1060°C for 120-210 minutes; keeping warm at 1040-1060°C for 120-210 minutes; heating from 1040-1060°C to 1115-1135°C for 30-60 minutes; keeping warm at 1115-1135°C for 10-50 minutes.

[0028] Most preferably, the raw material mixture is heated to 600°C for 30 to 60 minutes; heated from 600°C to 900°C for 60 to 120 minutes; kept at 900°C for 120 to 180 minutes; heated from 900°C to 1050°C for 120 to 210 minutes; kept at 1050°C for 120 to 210 minutes; heated from 1050°C to 1125°C for 30 to 60 minutes; kept at 1125°C for 10 to 50 minutes.

[0029] The technical solution of the present invention is described in detail below with specific embodiments, wherein the raw materials in the embodiments and comparative examples are specifically as follows, calculated by mass percentage:

[0030] Blast furnace slag: aluminum oxide (Al2O3) 11.49%, silicon dioxide (SiO2) 34.33%, iron oxide (Fe2O3) 0.46%, calcium oxide (CaO) 39.93%, magnesium oxide (MgO) 8.87%, potassium oxide (K2O) 0.52%, sodium oxide (Na2O) 0.52%, titanium dioxide (TiO2) 1.46%, loss on ignition is 1.14%, and the remainder is impurities.

[0031] Potassium feldspar: aluminum oxide (Al2O3) 8.74%, silicon dioxide (SiO2) 65.06%, iron oxide (Fe2O3) 0.12%, calcium oxide (CaO) 0.23%, magnesium oxide (MgO) 0.07%, potassium oxide (K2O) 12.41%, sodium oxide (Na2O) 2.66%, titanium dioxide (TiO2) 0.01%, loss on ignition is 0.40%, and the remainder is impurities.

[0032] Perlite tailings: aluminum oxide (Al2O3) 13.88%, silicon dioxide (SiO2) 71.08%, iron oxide (Fe2O3) 1.13%, calcium oxide (CaO) 0.99%, magnesium oxide (MgO) 0.81%, potassium oxide (K2O) 4.43%, sodium oxide (Na2O) 2.77%, titanium dioxide (TiO2) 0.10%, loss on ignition is 4.37%, and the remainder is impurities.

[0033] Glass powder: aluminum oxide (Al2O3) 2.11%, silicon dioxide (SiO2) 72.07%, iron oxide (Fe2O3) 0.10%, calcium oxide (CaO) 5.26%, magnesium oxide (MgO) 2.99%, potassium oxide (K2O) 1.33%, sodium oxide (Na2O) 13.01%, titanium dioxide (TiO2) 0.06%, loss on ignition is 0.70%, and the remainder is impurities.

[0034] Mujie soil: aluminum oxide (Al2O3) 36.28%, silicon dioxide (SiO2) 44.61%, iron oxide (Fe2O3) 1.10%, calcium oxide (CaO) 1.13%, magnesium oxide (MgO) 0.20%, potassium oxide (K2O) 0.52%, sodium oxide (Na2O) 0.65%, titanium dioxide (TiO2) 0.70%, loss on ignition is 14.50%, and the remainder is impurities.

[0035] Talc: aluminum oxide (Al2O3) 1.92%, silicon dioxide (SiO2) 34.08%, iron oxide (Fe2O3) 0.43%, calcium oxide (CaO) 1.67%, magnesium oxide (MgO) 36.24%, potassium oxide (K2O) 0.26%, sodium oxide (Na2O) 0.14%, titanium dioxide (TiO2) 0.07%, loss on ignition is 25.14%, and the remainder is impurities.

[0036] Feldspar: aluminum oxide (Al2O3) 19.74%, silicon dioxide (SiO2) 69.67%, iron oxide (Fe2O3) 0.12%, calcium oxide (CaO) 0.43%, magnesium oxide (MgO) 0.09%, potassium oxide (K2O) 3.04%, sodium oxide (Na2O) 4.51%, titanium dioxide (TiO2) 0.01%, loss on ignition is 0.35%, and the remainder is impurities.

[0037] Silica tailings: aluminum oxide (Al2O3) 11.34%, silicon dioxide (SiO2) 81.15%, iron oxide (Fe2O3) 1.08%, calcium oxide (CaO) 0.41%, magnesium oxide (MgO) 0.06%, potassium oxide (K2O) 3.03%, sodium oxide (Na2O) 1.73%, titanium dioxide (TiO2) 0.03%, loss on ignition 0.97%, and the remainder is impurities.

[0038] Kaolin: aluminum oxide (Al2O3) 32.28%, silicon dioxide (SiO2) 53.56%, iron oxide (Fe2O3) 0.27%, calcium oxide (CaO) 0.04%, magnesium oxide (MgO) 0.11%, potassium oxide (K2O) 1.01%, sodium oxide (Na2O) 0.62%, titanium dioxide (TiO2) 0.04%, loss on ignition is 11.65%, and the remainder is impurities.

[0039] Example 1

[0040] Calculated by mass percentage, the first raw material includes: 30% blast furnace slag, 30% feldspar, 20% perlite tailings, 10% glass powder, 5% wood clay, and 5% talc; the second raw material is a foaming agent, and the second raw material accounts for 0.2% of the first raw material.

[0041] The first raw material and the second raw material are mixed and ball-milled, and dried and powdered to obtain a raw material mixture, and then the raw material mixture is fired to obtain a bionic coral reef; Among them, the firing process is: heating the raw material mixture to 600°C for 30 minutes; heating from 600°C to 900°C for 90 minutes; keeping warm at 900°C for 150 minutes; heating from 900°C to 1050°C for 150 minutes; keeping warm at 1050°C for 150 minutes; heating from 1050°C to 1125°C for 40 minutes; keeping warm at 1125°C for 20 minutes.

[0042] Example 2

[0043] Calculated by mass percentage, the first raw material includes: 30% blast furnace slag, 30% potassium feldspar, 20% perlite tailings, 10% glass powder, 5% wood clay, and 5% talc; the second raw material is a foaming agent, and the second raw material accounts for 0.2% of the first raw material.

[0044] The first raw material and the second raw material are mixed, ball-milled, dried and powdered to obtain a raw material mixture, and then the raw material mixture is fired to obtain a bionic coral reef. The firing process is the same as that in Example 1.

[0045] Example 3 Calculated by mass percentage, the first raw material includes: 30% blast furnace slag, 25% feldspar, 25% perlite tailings, 8% glass powder, 7% wood clay, and 5% talc; the second raw material is a foaming agent, and the second raw material accounts for 0.2% of the first raw material.

[0046] The first raw material and the second raw material are mixed, ball-milled, dried and powdered to obtain a raw material mixture, and then the raw material mixture is fired to obtain a bionic coral reef. The firing process is the same as that in Example 1.

[0047] Example 4

[0048] Calculated by mass percentage, the first raw material includes: 35% blast furnace slag, 30% feldspar, 18% perlite tailings, 6% glass powder, 6% wood clay, and 5% talc; the second raw material is a foaming agent, and the second raw material accounts for 0.2% of the first raw material.

[0049] The first raw material and the second raw material are mixed, ball-milled, dried and powdered to obtain a raw material mixture, and then the raw material mixture is fired to obtain a bionic coral reef. The firing process is the same as that in Example 1.

[0050] Example 5

[0051] Calculated by mass percentage, the first raw material includes: 40% blast furnace slag, 10% feldspar, 30% perlite tailings, 10% glass powder, 5% wood clay, and 5% talc; the second raw material is a foaming agent, and the second raw material accounts for 0.2% of the first raw material.

[0052] The first raw material and the second raw material are mixed, ball-milled, dried and powdered to obtain a raw material mixture, and then the raw material mixture is fired to obtain a bionic coral reef. The firing process is the same as that in Example 1.

[0053] Comparative Example 1

[0054] In this comparative example, the amount of blast furnace slag used is insufficient.

[0055] Calculated by mass percentage, the first raw material includes: 15% blast furnace slag, 30% feldspar, 30% perlite tailings, 10% glass powder, 10% wood clay, and 5% talc; the second raw material is a foaming agent, and the second raw material accounts for 0.2% of the first raw material.

[0056] The first raw material and the second raw material are mixed, ball-milled, dried and pulverized to obtain a raw material mixture, and then the raw material mixture is fired to obtain a product. The firing process is the same as that in Example 1.

[0057] Comparative Example 2

[0058] In this comparative example, the amount of blast furnace slag used is excessive.

[0059] Calculated by mass percentage, the first raw material includes: 55% blast furnace slag, 12% feldspar, 18% perlite tailings, 5% glass powder, 5% wood clay, and 5% talc; the second raw material is a foaming agent, and the second raw material accounts for 0.2% of the first raw material.

[0060] The first raw material and the second raw material are mixed, ball-milled, dried and pulverized to obtain a raw material mixture, and then the raw material mixture is fired to obtain a product. The firing process is the same as that in Example 1.

[0061] Comparative Example 3

[0062] In this comparative example, the amount of perlite tailings used was excessive.

[0063] Calculated by mass percentage, the first raw material includes: 30% blast furnace slag, 10% feldspar, 45% perlite tailings, 5% glass powder, 5% wood clay, and 5% talc; the second raw material is a foaming agent, and the second raw material accounts for 0.2% of the first raw material.

[0064] The first raw material and the second raw material are mixed, ball-milled, dried and pulverized to obtain a raw material mixture, and then the raw material mixture is fired to obtain a product. The firing process is the same as that in Example 1.

[0065] Comparative Example 4

[0066] In this comparative example, no glass powder was added.

[0067] Calculated by mass percentage, the first raw material includes: 40% blast furnace slag, 30% feldspar, 20% perlite tailings, 5% wood clay, and 5% talc; the second raw material is a foaming agent, and the second raw material accounts for 0.2% of the first raw material.

[0068] The first raw material and the second raw material are mixed, ball-milled, dried and pulverized to obtain a raw material mixture, and then the raw material mixture is fired to obtain a product. The firing process is the same as that in Example 1.

[0069] Comparative Example 5

[0070] In this comparative example, the amount of glass powder used is excessive.

[0071] Calculated by mass percentage, the first raw material includes: 30% blast furnace slag, 20% feldspar, 20% perlite tailings, 20% glass powder, 5% wood clay, and 5% talc; the second raw material is a foaming agent, and the second raw material accounts for 0.2% of the first raw material.

[0072] The first raw material and the second raw material are mixed, ball-milled, dried and pulverized to obtain a raw material mixture, and then the raw material mixture is fired to obtain a product. The firing process is the same as that in Example 1.

[0073] Comparative Example 6

[0074] In this comparative example, the perlite tailings were insufficient.

[0075] Calculated by mass percentage, the first raw material includes: 45% blast furnace slag, 30% feldspar, 5% perlite tailings, 10% glass powder, 5% wood clay, and 5% talc; the second raw material is a foaming agent, and the second raw material accounts for 0.2% of the first raw material.

[0076] The first raw material and the second raw material are mixed, ball-milled, dried and pulverized to obtain a raw material mixture, and then the raw material mixture is fired to obtain a product. The firing process is the same as that in Example 1.

[0077] Comparative Example 7

[0078] In this comparative example, the amount of perlite tailings is insufficient, and the amount of glass powder is excessive to replace part of the perlite tailings.

[0079] Calculated by mass percentage, the first raw material includes: 30% blast furnace slag, 30% feldspar, 5% perlite tailings, 25% glass powder, 5% wood clay, and 5% talc; the second raw material is a foaming agent, and the second raw material accounts for 0.2% of the first raw material.

[0080] The first raw material and the second raw material are mixed, ball-milled, dried and pulverized to obtain a raw material mixture, and then the raw material mixture is fired to obtain a product. The firing process is the same as that in Example 1.

[0081] Comparative Example 8

[0082] In this comparative example, silica tailings were used instead of perlite tailings.

[0083] Calculated by mass percentage, the first raw material includes: 30% blast furnace slag, 30% feldspar, 20% silica tailings, 10% glass powder, 5% wood clay, and 5% talc; the second raw material is a foaming agent, and the second raw material accounts for 0.2% of the first raw material.

[0084] The first raw material and the second raw material are mixed, ball-milled, dried and pulverized to obtain a raw material mixture, and then the raw material mixture is fired to obtain a product. The firing process is the same as that in Example 1.

[0085] Comparative Example 9

[0086] In this comparative example, the amount of clay used was excessive.

[0087] Calculated by mass percentage, the first raw material includes: 30% blast furnace slag, 20% feldspar, 20% perlite tailings, 10% glass powder, 15% wood clay, and 5% talc; the second raw material is a foaming agent, and the second raw material accounts for 0.2% of the first raw material.

[0088] The first raw material and the second raw material are mixed, ball-milled, dried and pulverized to obtain a raw material mixture, and then the raw material mixture is fired to obtain a product. The firing process is the same as that in Example 1.

[0089] Comparative Example 10

[0090] In this comparative example, the amount of clay used was insufficient.

[0091] Calculated by mass percentage, the first raw material includes: 30% blast furnace slag, 30% feldspar, 23% perlite tailings, 10% glass powder, 2% wood clay, and 5% talc; the second raw material is a foaming agent, and the second raw material accounts for 0.2% of the first raw material.

[0092] The first raw material and the second raw material are mixed, ball-milled, dried and pulverized to obtain a raw material mixture, and then the raw material mixture is fired to obtain a product. The firing process is the same as that in Example 1.

[0093] Comparative Example 11

[0094] In this comparative example, conventional kaolin was used instead of Kibbutz clay.

[0095] Calculated by mass percentage, the first raw material includes: 30% blast furnace slag, 30% feldspar, 20% perlite tailings, 10% glass powder, 5% kaolin, and 5% talc; the second raw material is a foaming agent, and the second raw material accounts for 0.2% of the first raw material.

[0096] The first raw material and the second raw material are mixed, ball-milled, dried and pulverized to obtain a raw material mixture, and then the raw material mixture is fired to obtain a product. The firing process is the same as that in Example 1.

[0097] The dry specific gravity and wet specific gravity of the bionic coral reefs obtained in Examples 1-5 and Comparative Examples 1-11 were calculated, and the pore size, water absorption rate and water seepage rate were tested, wherein the test method was as follows:

[0098] Aperture test method: Cut off the epidermis of the bionic coral reef to make it flat, use a vernier caliper to measure the values ​​of the smallest complete hole and the largest complete hole with a complete cross section and record them.

[0099] Water absorption test method: Prepare the sample according to the requirements of Chapter 4 of GB / T 3810.3-2006 "Test methods for ceramic tiles Part 3: Determination of water absorption, apparent porosity, apparent relative density and bulk density". The sample size must be greater than 100mm×100mm×80mm. Put it in a vacuum container so that the samples do not touch each other. Add enough water to cover the sample and raise it by 5cm. Vacuum to 10kPa ±1kPa and maintain it for 30min, then stop vacuuming. Let the sample soak for 15min, then take it out and place it on a suspended bracket. Blow it with 0.8kg of compressed air for 3min at a distance of 10cm from the upper surface of the sample, then weigh it immediately and record it. Calculate the water absorption according to the method specified in 6.1 of GB / T 3810.3-2006.

[0100] Water seepage rate test method: cut off the epidermis of the bionic coral reef to make it flat, use a dropper to transfer 1mL of water, and evenly drop it on the surface of the coral reef sample. Observe the water seepage with your eyes. If all the water seeps in within 5 seconds, the seepage rate is fast. If all the water seeps in between 6s-20s, the seepage rate is medium. If all the water seeps in after 21s-60s, the seepage rate is slow. If there is no obvious change in the water surface after 60s, it is judged that there is basically no water seepage.

[0101] The test results are shown in Table 1 below.

[0102]

[0103] According to the test results, the product prepared by the present invention has a small dry specific gravity when it has not absorbed water, which is convenient for transportation, and has a large water absorption rate and a fast water absorption speed. It can quickly absorb water and sink to the bottom during installation, and its multi-through-hole structure facilitates underwater microorganisms to attach to the holes. During the firing process, the calcium oxide in the formula reacts with the silicon dioxide to generate calcium silicate at the firing temperature of the present invention, and the firing temperature of the present invention will not cause thermal decomposition of calcium silicate. Calcium silicate is a substance that long-spined sea stars do not like to chew, and calcium silicate is non-toxic and insoluble in water. It is very suitable for use as a bionic coral reef and can exist for a long time.

[0104] Comparative Example 1 reduces the amount of blast furnace slag. Since calcium oxide in blast furnace slag has the effect of reducing the firing temperature of the formula, insufficient blast furnace slag leads to a high firing temperature. In the firing curve of the present invention, through holes cannot be effectively formed, resulting in a large dry specific gravity and low water absorption rate of the product. According to the data in Table 1, the wet specific gravity of the product of Comparative Example 1 after absorbing water is still smaller than the water density, and it cannot be used as a bionic coral reef.

[0105] Comparative Example 2 increases the amount of blast furnace slag and reduces the firing temperature of the formula. Within the firing curve of the present invention, the product will melt again after forming through holes and cause blockage, resulting in a decrease in the final water absorption rate of the product. According to the data in Table 1, the wet specific gravity of the product in Comparative Example 2 is too small and cannot be used as a bionic coral reef.

[0106] The present invention preferably uses perlite tailings, which have a high silicon content and can improve the green body structure and enhance the formula stability. However, glass powder cannot replace perlite tailings, as this will cause the through holes of the product to be clogged, and the product will lose the characteristics of multiple through holes and fast water absorption. Tailings with similar components or functions can also replace perlite tailings.

[0107] The silicon in glass powder has a different crystalline structure from that in feldspar or tailings, and the calcium oxide and sodium oxide contents therein are different, which results in a low firing temperature for glass powder and a higher firing temperature for feldspar or tailings relative to glass powder. The silicon in glass powder is an amorphous structure, with disordered atomic arrangement and lack of long-range order, resulting in low thermal stability; and the glass contains more calcium oxide and sodium oxide, which will destroy the original structure, resulting in a low overall firing temperature. The silicon dioxide in feldspar or perlite tailings is a crystalline structure, with orderly atomic arrangement, forming a stable three-dimensional network structure, and a lower calcium oxide content, resulting in a higher overall firing temperature.

[0108] Comparative Example 3 increases the amount of perlite tailings. The silicon dioxide in perlite is a crystalline structure with highly ordered atomic arrangement to form a stable three-dimensional network structure, which requires higher energy to be destroyed. In addition, the sodium oxide content of the entire formula is low, and sodium oxide has a fluxing effect, which will reduce the sintering temperature of the formula. A low sodium oxide content will lead to an increase in the sintering temperature of the formula, and through holes cannot be effectively formed, which is similar to the situation in Comparative Example 1.

[0109] Comparative Example 4 omits the glass powder, which also results in a lower sodium oxide content in the formula. The lack of the flux causes the sintering temperature of the formula to increase, which is similar to the situation in Comparative Examples 1 and 3.

[0110] Comparative Example 5 greatly increases the amount of glass powder used. In contrast to the situation in Comparative Example 4, the increased content of calcium oxide and sodium oxide in the formula will lead to a lower firing temperature of the formula. Within the firing curve of the present invention, the product will be clogged after the through holes are formed, resulting in a lower final water absorption rate of the product. According to the data in Table 1, the wet specific gravity of the product in Comparative Example 5 is too small and cannot be used as a bionic coral reef.

[0111] In Comparative Example 6, the amount of perlite tailings used is reduced, the silicon dioxide content in the formula system is reduced, and the calcium oxide content is increased, resulting in a decrease in the firing temperature, clogging of the pores of the product, and a decrease in the water absorption rate.

[0112] In Comparative Example 7, the amount of glass powder is increased to replace part of the perlite tailings, which will lead to an increase in the glass phase during the firing process. The formula has strong fusibility. Under the same firing system, the most intuitive manifestation is that the firing temperature is reduced. In the case of the firing curve of the present invention, the product has clogged pores, resulting in low water absorption.

[0113] Comparative Example 8 uses silica tailings instead of perlite tailings. Since the silica tailings contain a higher silicon dioxide content and relatively lower calcium oxide and sodium oxide components, the sintering temperature of the formula increases. Under the same sintering curve, the pores are not opened in time, resulting in low water absorption.

[0114] Comparative Example 9 increases the amount of wood-block soil, that is, the amount of clay in the formula is high, which makes the formula fluidity poor and is not conducive to production. Secondly, the content of aluminum oxide in the formula increases, which directly leads to an increase in the firing temperature of the formula. Under the same firing temperature conditions, the pores cannot be fully opened, resulting in low water absorption.

[0115] Comparative Example 10 reduces the amount of wood-block soil, and the low clay content in the formula makes the formula less viscous and easy to sink to the bottom, resulting in unstable formula in actual production. Secondly, the content of aluminum oxide in the formula is reduced, which directly leads to a decrease in the sintering temperature of the formula, blocking the pores and causing low water absorption.

[0116] In Comparative Example 11, kaolin is replaced with mochiko. From the composition point of view, the iron, titanium and calcium contents of kaolin are all lower than those of mochiko, and these ingredients are all helpful in lowering the firing temperature. Their absence will cause the formula firing temperature to be slightly higher, the pores to not be fully opened, and the water absorption rate to be poor.

[0117] The embodiments provided by the present invention are described in detail above. Specific examples are used herein to describe the principles and implementation methods of the present invention, and the description of the above embodiments is only used to help understand the core idea of ​​the present invention. It should be pointed out that for ordinary technicians in this technical field, without departing from the principles of the present invention, the present invention can also be improved and modified in a number of ways, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.

Claims

1. A bionic coral reef, characterized in that: The raw materials for making the bionic coral reef include a first raw material and a second raw material; In the first raw material, calculated by mass percentage, the first raw material includes 30-45% of blast furnace slag, 10-30% of feldspar, 15-30% of tailings, 5-10% of glass powder, 5-10% of clay and 5-10% of talc; The second raw material includes a foaming agent, and the foaming agent accounts for 0.2-0.6% of the mass of the first raw material.

2. The bionic coral reef according to claim 1, characterized in that: The components in blast furnace slag are calculated by mass percentage. The silicon dioxide content in blast furnace slag is ≥30%, the aluminum oxide content is ≥10%, and the calcium oxide content is ≥30%.

3. The bionic coral reef according to claim 1, characterized in that: The components in the tailings are calculated by mass percentage, with the silicon dioxide content ≥60%, the aluminum oxide content ≥10%, the potassium oxide content ≥3%, and the sodium oxide content ≥2%.

4. The bionic coral reef according to claim 3, characterized in that: Tailings include perlite tailings.

5. The bionic coral reef according to claim 1, characterized in that: The components in the clay are calculated by mass percentage, and the silicon dioxide content in the clay is ≥40%, the aluminum oxide content is ≥35%, the iron oxide content is ≥1%, and the titanium dioxide content is ≥0.5%.

6. The bionic coral reef according to claim 5, characterized in that: Clay includes woodblock soil.

7. The bionic coral reef according to claim 1, characterized in that: The components in feldspar are calculated by mass percentage. The total amount of potassium and sodium elements in feldspar is ≥7% and the potassium content is ≥3%.

8. The bionic coral reef according to claim 7, characterized in that: Feldspar includes potassium feldspar powder with a potassium content ≥ 10%.

9. The bionic coral reef according to any one of claims 1 to 8, characterized in that: The blowing agent includes silicon carbide.

10. A method for making a bionic coral reef, characterized in that: The bionic coral reef as claimed in any one of claims 1 to 9 is prepared as follows: The first raw material and the second raw material are mixed and ball-milled, and dried and powdered to obtain a raw material mixture, and then the raw material mixture is fired to obtain a bionic coral reef; The firing process is as follows: heating the raw material mixture to 600-650°C for 30-60 minutes; heating from 600-650°C to 890-910°C for 60-120 minutes; keeping warm at 890-910°C for 120-180 minutes; heating from 890-910°C to 1040-1060°C for 120-210 minutes; keeping warm at 1040-1060°C for 120-210 minutes; heating from 1040-1060°C to 1115-1135°C for 30-60 minutes; keeping warm at 1115-1135°C for 10-50 minutes.

Citation Information

Patent Citations

  • Eco-friendly artificial mimic coral reef

    CN109169459A

  • Cement and coral sand mixed type substratum and manufacturing and application method thereof

    CN114467806A

  • Foamed ceramic produced by iron and steel plant tailings and preparation method thereof

    CN110511052A

  • Formula and preparation process of artificial corallite

    CN110734277A

  • 3D printing porous coral and preparation method thereof

    CN113831110A

Cited By

  • An ecological friendly multifunctional double-layer sand protection dike and a construction method thereof

    CN122610477A